Total Body Fat Content versus BMI in 4-Year-Old Healthy Swedish Children - Elisabet Forsum; Eva Flinke Carlsson; Hanna Henriksson; Pontus Henriksson; Marie Löf (Hindawi Limited, 2013)
Childhood overweight and obesity, a worldwide problem, is generally identified using BMI (body mass index). However, this application of BMI has been little investigated in children below 5 years of age due to a lack of appropriate methods to assess body composition. Therefore, we used air displacement plethysmography (ADP) to study 4.4-year old boys and girls since this method is accurate in young children if they accept the requirements of the measurement. The purpose was to analyze the relationship between BMI and body fat in these children. Body composition was assessed in 76 (43 boys, 33 girls) of the 84 children brought to the measurement session. Boys and girls contained 25.2±4.7 and 26.8±4.0% body fat, respectively. BMI-based cut-offs for overweight could not effectively identify children with a high body fat content. There was a significant (P<0.001) but weak (r=0.39) correlation between BMI and body fat (%). In conclusion, requirements associated with a successful assessment of body composition by means of ADP were accepted by most 4-year-olds. Furthermore, BMI-based cut-offs for overweight did not effectively identify children with a high body fatness and BMI explained only a small proportion of the variation in body fat (%) in this age group.